Biological Effect of Heavy Metal in Drinking Water samples of Western Uttar Pradesh region in India - Gaur Sandeep, Agrawal Sangita, Saxena Sandeep Kumar, Goyal Rakhi, Kumar Dinesh (Journal of Applied Pharmaceutical Science)
Drinking water is a basic requirement for life and a determinant of standard of living. Poor water quality problem has also been observed in more number of habitations. Drinking water, in adequate quantity with safe quality is a basic requirement for life and a determinant of standard of living. Certain health problems are associated with people due to presence of excess of heavy metals and other impurities. The present study was conducted to analyze the various parameters of ground water in Uttar Pradesh India and to check its fitness for drinking. It will also clarify the health hazards imposed on the population of this state. The water samples are collected from Aligarh, Bulandshar, Merrut, Muzaffar Nagar & Saharanpur zone of the Western U.P. region. Ten samples of ground water were collected from each of the five regions during the pre-mansoon (Jan-Feb) and post-mansoon (Sept-Oct) seasons. The pH was estimated by pH meter, acidity, alkalinity, sulphates, chorides, Total hardness (Ca & Mg) were determined by titration methods. The total suspended solid was calculated by the formula. The heavy metals like Mn, Al, Ba, Cd, Cr, Co, Cu, Fe and Pb were determined in the ground water samples by ICP mass spectroscopy. The concentrations of heavy metals, pH, alkalinity, sulphate, chloride, TDS & Total Hardness (TH) were compared with the standards by BIS for Drinking water (IS 10500:2004). The results shows that water pH of all the five regions showed no remarkable variation from the BIS recommended value of pH (6.5-8.5). The alkalinity was above the BIS desirable level of 200mg/l in all the samples, but was less than the maximum permissible limit. The Drinking water of all the regions contains higher amounts of TDS than the desirable limits. Maximum TDS was detected in Aligarh (780-820mg/litre). The ground water of Saharanpur region shows total hardness to be above the BIS desirable level of 300mg/l. The chloride content was above the BIS desirable level of 250mg/l in Aligarh only. The sulphate content was highest in Aligarh (223mg/l). The Cd, Cr, &Pb content of all the five regions of Uttar Pradesh showed higher the BIS permissible limits of 0.003, 0.05 and 0.01mg/l respectively. The content of Mn, Ba, Cu, Co & Fe are within the permissible limit of BIS standards for drinking water.
Keywords: Ground water, Hydro-chemical analysis, heavy metals, ICP mass spectroscopy.